2014
DOI: 10.1007/s10120-014-0411-x
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex interactions in gastric cancer incidence and mortality trends in Korea

Abstract: Background The incidence and mortality of gastric cancer have declined rapidly over the past few decades, but reverse trends in the young generation's differential between sexes in some races have been reported in recent years. To investigate whether this divergent trend can be observed in Korea, a country with the highest incidence in the world, age-and sex-specific incidence and mortality trends were evaluated. Methods Gastric cancer incidence data for the years 1999-2010 and mortality data for the years 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 29 publications
3
49
0
1
Order By: Relevance
“…In a study performed in the United States, the noncardiac GC incidence per 100,000 person-years among white adults aged 25 to 39 years increased from 0.27 in 1977-1981 to 0.45 in 2002-2006 [11]. In contrast, the trend for ages 20-39 expressed in annual percent change decreased at a rate of -3.7% and -0.8% in males and females, respectively, from 1999 to 2010 in South Korea [12].…”
Section: Epidemiologymentioning
confidence: 90%
“…In a study performed in the United States, the noncardiac GC incidence per 100,000 person-years among white adults aged 25 to 39 years increased from 0.27 in 1977-1981 to 0.45 in 2002-2006 [11]. In contrast, the trend for ages 20-39 expressed in annual percent change decreased at a rate of -3.7% and -0.8% in males and females, respectively, from 1999 to 2010 in South Korea [12].…”
Section: Epidemiologymentioning
confidence: 90%
“…24 The age-adjusted incidence rates per 100 000 person-year from 1999 to 2010 were 7.40 males and 8.33 females within the ages of 20-39 years, and these increased up to 73.11 males and 35.13 females within the ages of 40-54 years. 25 Data from GLOBOCAN 2012, produced by the International Agency for Research on Cancer (IARC), showed that the age-standardized incidence rates per 100 000 for gastric cancer in Korea were 5.7 within the ages of 15-39 years, and it increased to 30 within the ages of 40-44 years. There is no study to evaluate the incidence of gastric cancer by age in patients with dyspepsia in Korea.…”
Section: Diagnosis Of Functional Dyspepsiamentioning
confidence: 99%
“…1 Although improved throughout the last decades, the prognosis is still poor. Whereas the majority of patients with early cancers can be cured by surgery alone, the median overall survival for patients diagnosed in a metastatic stage is less than one year.…”
Section: Introductionmentioning
confidence: 99%